Un element quadrilateral de plaque base sur one formulation mixte-hybride avec projection en cisaillement - Ayad, Rezak; Batoz, Jean-Louis; Dhatt, Gouri (European Journal of Computational Mechanics, 1995)
This work deals with the formulation of a new 4-node quadrilateral element for the linear analysis of plate bending with transverse shear effect. This formulation is based on a variational hybrid-mixed model called MiSP (Mixed Shear Projected). The approximation of the shear forces results from that of bending moments with an explicit satisfaction of two of the three equilibrium equations. The TS deformations are defined in terms of the edge deformations which are projected on the nodal degrees of freedom. The convergence of the element is checked on a series of constant and rigid mode patch-tests, and its precision is evaluated on two series of benchmark examples related to skewed and circular plates.